2003
DOI: 10.1097/01.ccm.0000089638.83803.b2
|View full text |Cite
|
Sign up to set email alerts
|

Discrepancies between ordered and delivered concentrations of opiate infusions in critical care

Abstract: The concentration of two thirds of infusions prepared for clinical use was outside accepted industry standards. These findings are likely to be broadly representative of intravenous drug administration in hospitalized children and pediatric pharmacokinetic studies. Further study of the causes and clinical impact is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
49
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(58 citation statements)
references
References 22 publications
7
49
0
1
Order By: Relevance
“…Adapa et al 11 reported that preparing infusions at the bedside in this emergent simulation resulted in an odds ratio of 17.0 (95% CI, 5.2-55) for making a medication error compared with preparing the infusions in a calmer environment or having the infusions prepared in the pharmacy. Other evidence [12][13][14][15] has highlighted the error-prone nature of preparing critical infusions at the bedside, including vasopressors and opioids. Task analysis 16 has identified a total of 41 potential steps in the process of preparing a drug infusion, providing 41 opportunities for error during the fast-paced environment of medical emergencies.…”
Section: Simulationmentioning
confidence: 99%
“…Adapa et al 11 reported that preparing infusions at the bedside in this emergent simulation resulted in an odds ratio of 17.0 (95% CI, 5.2-55) for making a medication error compared with preparing the infusions in a calmer environment or having the infusions prepared in the pharmacy. Other evidence [12][13][14][15] has highlighted the error-prone nature of preparing critical infusions at the bedside, including vasopressors and opioids. Task analysis 16 has identified a total of 41 potential steps in the process of preparing a drug infusion, providing 41 opportunities for error during the fast-paced environment of medical emergencies.…”
Section: Simulationmentioning
confidence: 99%
“…6 The process of ordering, preparing, and administering continuous medication infusions offers several opportunities for error. 4,[7][8][9] Providing the correct weight-adjusted dose (at an acceptable rate, concentration, and volume) usually requires a multivariable calculation; moreover, a new calculation must be performed whenever the dose is changed. The need for individualized concentrations makes drip preparation a high-frequency and time-consuming task for the pharmacy.…”
mentioning
confidence: 99%
“…15 Direct assessment of intravenous drug infusions received by patients has suggested that up to 65% of infusions have unacceptable concentrations by industry standards despite routine safety practises. [16][17][18][19][20][21][22][23] We performed a systematic evaluation of the preparation process for intravenous infusions to identify factors associated with preventable medication errors.…”
mentioning
confidence: 99%